2016
DOI: 10.1007/s10021-016-9969-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Top-Down and Bottom-Up Controls on the Collapse of Alewives (Alosa pseudoharengus) in Lake Huron

Abstract: Food web models are powerful tools to inform management of lake ecosystems, where top-down (predation) and bottom-up (resource) controls likely propagate through multiple trophic levels because of strong predator-prey links. We used the Ecopath with Ecosim modeling approach to assess these controls on the Lake Huron main basin food web and the 2003 collapse of an invasive pelagic prey fish, alewife (Alosa pseudoharengus). We parameterized two Ecopath models to characterize food web changes occurring between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 49 publications
(21 reference statements)
0
31
0
Order By: Relevance
“…In Lake Huron, biomass of alewives, the preferred prey of stocked Pacific salmon, collapsed between 2002 and 2003, resulting in declining recreational harvests of salmon. Statistical analysis did not identify a clear cause of the crash (Bunnell et al ), while food web and fisheries models suggested a combination of top‐down and bottom‐up causes (He et al ; Kao et al ).…”
mentioning
confidence: 99%
“…In Lake Huron, biomass of alewives, the preferred prey of stocked Pacific salmon, collapsed between 2002 and 2003, resulting in declining recreational harvests of salmon. Statistical analysis did not identify a clear cause of the crash (Bunnell et al ), while food web and fisheries models suggested a combination of top‐down and bottom‐up causes (He et al ; Kao et al ).…”
mentioning
confidence: 99%
“…Drivers of offshore fish community production He et al (2015); Kao, Adlerstein, and Rutherford (2016); Riley et al (2008) Ecological models…”
Section: Structural Attributesmentioning
confidence: 99%
“…Implications of density-dependent top-down effects of planktivore grazing and piscivore predation on ecosystem function and adaptive capacity Negus, Schreiner, and Halpern (2008); Kao et al (2016) Ecological models Drivers of changes in zooplankton community structure and impacts of these changes on food-web structure and adaptive capacity of the system Barbiero et al (2012); Barbiero, Lesht, and Warren (2014) (Casini et al, 2009;Daskalov, Grishin, Rodionov, & Mihneva, 2007);…”
Section: Natural Processesmentioning
confidence: 99%
“…; Kao et al. ). In Lake Huron, the Alewife population collapse was likely due to predation by stocked Pacific salmon Oncorhynchus spp.…”
mentioning
confidence: 97%
“…Understanding salmonid and Walleye Sander vitreus predation on forage fish has become an important research topic because of concern regarding declining forage fish populations in some lakes and because many salmonids are stocked and predator numbers can, to some extent, be manipulated to be in balance with the prey supply (Kitchell et al 1994;Riley et al 2008). Declining forage fish populations, and specifically Alewife Alosa pseudoharengus populations, have become a concern in the Laurentian Great Lakes over the past several decades, following the collapse of Alewife populations in Lake Huron in the early 2000s (Dettmers et al 2012;Kao et al 2016). In Lake Huron, the Alewife population collapse was likely due to predation by stocked Pacific salmon Oncorhynchus spp.…”
mentioning
confidence: 99%